The Factors of Rice Farmers’ Poverty in Indonesia: The Perspective of Land Conversion, Land Ownership Area, and Agriculture Technologi - Septian Widyanto; Leksono Probo Subanu (Universitas Gadjah Mada, 2023)
Rice is very important as Indonesia’s main staple. It contributes a lot to the national expenditure where more than 80% of households of every social class consumed rice. There is a high demand level for rice but there is a limited number of farmers. Of 70% of households in rural that work in the agricultural sector, only 50% grow rice, and most of them are poor farmers. Almost 52% of Indonesia’s rice is produced at Java Isle. However, production growth is only 0,7% given the rapidly increasing number of people and land conversion over the past 7 years. Most Indonesian farmers are classified as small farmers has average land ownership of only less than 0.5 hectares, making them can’t innovate and only can fulfil their basic needs without saving for investment. This is made worse by around 35% of farmers don’t own their land. Technology usage also become an issue where 85% of farmers don’t use internet and 45% are not used in using mechanical technology. The purpose of this research is to find the effect of paddy land conversion, land ownership area, and agriculture technology on farmer’s poverty in Indonesia. By using multiple regression method on 6 independent variables data from all Indonesia provinces, we found that the most significant variable to reduce farmer’s poverty is land ownership area. The statistical result is supported and cross-checked by data and related policies from literature review, and interview with some stakeholders from Ministry of Agriculture, local government, paddy farmer representative, and agriculture instructor.